Association between modifiable lifestyle and the prevalence of atrial fibrillation in a Chinese population: Based on the cardiovascular health score. Issue 11 (21st August 2017) - Yang, Yiheng; Han, Xu; Chen, Yue; Gao, Lianjun; Yin, Xiaomeng; Li, Huihua; Qiu, Jing; Wang, Youxin; Zhou, Yong; Xia, Yunlong
Abstract : Background: The Cardiovascular Health (CVH) Score was comprised of a series of modifiable lifestyle and health factors, which was published by American Heart Association in 2010. Its relationship with atrial fibrillation (AF) remains unclear. Hypothesis: Individuals with a higher CVH Score had a lower risk of AF. Methods: Participants ≥40 years of age were recruited from the Jidong community. Information regarding the following 7 CVH metrics, including smoking, body mass index, diet, physical activity, total cholesterol, and fasting blood glucose, were collected. AF was confirmed with a standard 12‐lead electrocardiography or based on the patients' medical histories. A multivariable logistic regression model was used to evaluate the relationship between ideal CVH and AF prevalence. Results: This study included 4477 individuals, among whom 48 had AF (1.07%). Overall, participants with higher ideal components scores had a lower risk of AF (odds ratio [OR]: 0.78; 95% confidence intervals [CI]: 0.62‐0.97; P trend = 0.024). Subgroup analyses showed that the trend was consistent in the male participants ages 40 to 60 years. Moreover, patients with 5 to 7 ideal components or 3 to 4 ideal components were associated with 57% and 59% reduced risks for AF, respectively. We also detected a significant association between ideal health factors and the prevalence of AF (OR: 0.79; 95% CI: 0.68‐0.93; P  = 0.004). Conclusions: Ideal health behavior and factors are associated with lower prevalence of AF in a community‐based population. Improving healthy behavior and these factors may be beneficial to decrease the prevalence of AF.